THE READER WITH “A LAMP AT THE CROSSROADS” : (Kišʼs concepts of the reader and Kiš as the reader) (Heritage, 2021)
Pictured as an introduction into the study of the same name due to be published in the book Some Real And Possible Worlds, this paper  focuses on Kiš as the reader of the works of others and his own works,  as well as on the types of readers in his poethics. That is where the writerʼs concept, i. e. the concepts of readers originate from. (The study consists of the following sections: 1. The reader and narrative metalepsis in the novel Mansarda, 2. The naive and insightful reader in Garden, Ashes, and Early Sorrows, 3. The ideal reader: Hourglass  4. Muromancy.  Readers of the marks on the wall in the prose of Danilo Kiš  5. The reader as an interpreter and the interpreter as a reader,  6. Kišʼs explicit concept/concepts of the reader.)Although his understanding is not expressed as a firm theoretical system, thus the concept is spoken about in a wider sense, the research confirms that Kiš was one the most curious readers of his time, a writer who intensively reflected on reading, who knew well the old methodological orientations in the reading theory and followed the contemporary ones. By adopting specific terminology and typology of reading theory and modifying it according to his own writing and reading experience, by themetising the act of reading in his prose and characterising his heros by means of what they read, Kiš demonstrated astonishing inventiveness and research passion. He already showed it in the novel Mansarda, which points out those problems of reading that will be actualised and systematised by classic narratology but cleared up only later by post-classic narratology: narration in the first person and duplication/replication of the author’s I, the problem of boundary beetween life and literature, narrative metalepsis etc.
Keywords: Key words: Kiš, reader, author, hero, (auto)biography, reading theories, duplication/ replication of the author’s I, metalepsis, life, literature.